Why do we watch what we watch? explaining film import choices of invidual countries among different production sources. - Sim, Clarice Chwei Lin. (2008)
This study examines the theatrical film import choices of individual countries over nine country production sources, namely the US, Italy, France, UK, India, Russia, Germany, Japan and Hong Kong. An empirical model consisting of measures of cinema market scale, cultural distance, linguistic similarity and geographic proximity is devised to explain the quantities of movies imported by countries over a range of export sources. Film import data of numerous countries, from 1970 to 1999, are drawn from the UNESCO statistical databank and subject to regression analysis. Various regression models are executed using different sets of film import data, which contain, respectively, the 1997 importer-country cross-section and a longitudinal set comprising 14 years’ importer-country cross-sections. The various regression analyses show that the frequency of film imports by an importing country from a production source significantly increases in the exporter’s domestic cinema economy and the importer’s affluence level. Likewise, a decrease in the cultural distance and the sharing of a common language between traders intensifies film import quantities, while locational adjacency reduces the level of film imports from an exporter. A time trend examination shows that global film flow has decreased in terms of the number of films over the years.